Sustainable feminisms - Sarker, Sonita, 1961- (Advances in gender research ;, 2007)
This volume illuminates the encounter of feminist activism with scholarship in political science, cultural studies, sociology, ethnic studies, and economics. The essays contribute images of the forces that lead to the development of many different kinds of feminisms and womens movements across the globe in the 20th century and recently. They explore the cultural constructions and legitimations of sustainability during the processes through which various agents interpret the relevance of feminisms for their social and political initiatives. The volume offers new dimensions on the relationships across time and place among activisms and scholarships, as ways to contemplate how feminisms are sustainable and whether there is a future beyond sustainability. This book gives a genealogical account of various different kinds of feminisms. It offers new dimensions on the relationships across time and place among activisms and scholarships. It investigates and discusses how feminisms are sustainable.